"Big Data" in neuroscience: open door to a more comprehensive and translational research. Issue 1 (December 2016) - Lloret-Villas, Audald; Daudin, Rachel; Le Novère, Nicolas
Abstract The International Symposium "Advances in Systems Biology in Neurosciences" was held in February 2015 in Geneva. A hundred scientists with a variety of expertise gathered around the theme of human brain complexity and cognitive disorders. Through a series of lectures and poster sessions, the symposium showcased state-of-the-art high-throughput biotechnologies, supercomputers and neuroimaging, and illustrated the latest advances in systems approaches to tackle Neurosciences and Neurodegenerative disorders. The meeting highlighted the power of big data to understand complex pathologies and also the need for more open and integrated data.